(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
Borderline personality disorder (BPD) is a condition of marked instability in affect, behavior, self-image, and relationships. Psychotherapy is the first-line treatment for BPD, with greater accumulated evidence of efficacy for Dialectic Behavioral Therapy (DBT). A pilot study indicated only one specific publication about DBT in Brazil. Therefore, we conducted a systematic review to investigate the Brazilian scientific frame on BPD, considering knowledge areas and the Brazilian regions where studies were conducted over the last 30 years. Among the 60 articles included in this review, 40 were related to therapeutic intervention (psychoanalytic based approaches, n=33; CBTs, n=5; existential therapies, n=2), 8 were related to Neurophysiology, and 5 to Neuropsychopharmacology. The municipalities of São Paulo and Rio Grande do Sul conducted 78% of the studies. We discuss the Brazilian scientific field on DBT, evidence based treatments and their research and possibilities.